Tokat merkez ilçede kadastro ve imar çalışmalarında karşılaşılan sorunlar ve çözüm önerileri - Susam, Tekin (Fen Bilimleri Enstitüsü, 1996)
Bu çalışmada, Tokat merkez ilçe'de, kadastro-imar çalışmalarında karşılaşılan genel sorunlar ele alınarak en ideal çözüm yolları araştırılmıştır. Bu sorunlar içerisinde hem imar ve hem de kadastro çalışmalarının ilk temelini teşkil eden 1930 grafik kadastro çalışması ele alınarak geniş kapsamlı olarak incelenmiştir. Bu inceleme neticesinde sözkonusu çalışma kapsamında kalan kadastro parselleri ile ilgili yapılan teknik işlemlerde büyük problemlerle karşılaşıldığı anlaşılmıştır. 1930 kadastro çalışmasının koordinat sistemi ile 1963 yılında oluşturulan yeni kadastro koordinat sistemi arasında herhangi bir ilişkinin olmaması da sorunun temelini teşkil etmektedir. Bu iki sistem arasında ilişki kurmak amacıyla dönüşüm parametreleri hesaplanmıştır. Bu dönüşüm parametrelerinin söz konusu kadastro çalışması ile ilgili sorunlar için kesin çözüm olamayacağı sonucuna varılmıştır. Kesin çözüm olarak şehrin merkezini kapsayan bu eski grafik kadastro çalışmasının yenilenmesi önerilmiştir. 1983 yılına kadar süregelen kadastro-imar koordinat birliğinin 1983 te nasıl bozulduğu incelenmiştir. Bu inceleme sonucunda da İller Bankasının kontrol sorumluluğunu gereği gibi kullanmadığı ortaya çıkmıştır. Çünkü 1983 yılında yanlış olduğu kabul edilen 1963 yılı nirengi ağı, 1986 yılında tekrar temel alınmış, 1989 yılında ise 1983 yılında oluşturulan koordinat sistemi temel alınarak, yeni ara nirengiler ve poligon noktaları tesis edilmiştir. Kadastro koordinat sistemi ile ülke koordinat sistemi arasında dönüşüm amacıyla daha önce kullanılan, birbirine çok yakın üç özdeş noktadan hesaplanmış dönüşüm parametreleri, uygun dağılımdaki 13 özdeş nokta kullanılarak yeniden hesaplanmıştır. Kadastro ve imar değişikliklerinde, plan homojenliğinin bozulması irdelenerek bu konularda uyulması gereken sistemler önerilmiştir. Tokat ana nirengi ağı ele alınarak dengeleme hesapları bilgisayar ortamında yeniden yapılmıştır. Farklı zamanlarda yapılan herbir ağ önce kendi içinde dengelenmiş daha sonra bütün olarak dengelenmiştir. Bu hesaplar neticesinde temel nirengi ağ ölçülerinin uyuşumsuz olmadığı anlaşılmıştır. 1983 yılında bozulan Tokat'taki koordinat birliğinin tekrar sağlanması için ülke koordinat sisteminin temel alınması gerektiği vurgulanmıştır.

In this work, the general cadastre and planning problems in city were studied and the best solution ways were researched. In these problems, some relations were drawn between the 1930s cadastre work, that is the base of both cadastre and city planning, and the new cadastre coordinate system. Transformation parameters were calculated among cadastre coordinate system, planning coordinate system and National Coordinate System by using Helmert's Similarity Transformation Method. Finaly, the changes in the cadastre work and the city planning were studied and the systems to be followed in these subjects were proposed. The first cadastre work in Tokat was done in 1930's. This work hasn't got a relation with neither new cadastre coordinate system nor National Coordinate System. It was understood that this cadastre work is insufficient for today's needs. With the purpose of setting a relation between old and new cadastre coordinate systems that was set up in 1963, the transformation parameters were calculated. As it is known, there must be at least two points whose coordinates are known in each two coordinate systems in order to set up a relation between two coordinate systems. But, there were no points such as these. In this work, eight points were selected. Each of them is the corner of historical buildings. These eight points were coordinated in both old and new cadastre coordinate system. By using these coordinates, the following transformation parameters were computed. A" = 0.9998377496 A12= 0.0010526892 Aoi = 18088.1296531473 Ao2= 21045.3742893958 However, there are more points whose coordinates exist in both cadastre and National Coordinate System, only the coordinates of three points have been used in order to transformation between these two coordinate systems. Also these three points are very close to each other. In this work, thirteen points were determined and their National Coordinates were taken from Cadastre General Office. The locations of these points in Tokat main triangulation network were illustrated in figure 1. DC Figure 1 : The locations of points that belong to both Tokat Main Triangulation Network and National Coordinate System By using the coordinates of these thirteen points in each coordinate system, the following transformation parameters were computed. An = 0.9999882240 A12 = -0.0063054804 Ao! = 4435083.2314920560 Ao2= 516373.5577646488 In addition, the relation between cadastre and planning coordinate system was studied. In this study, seventeen points whose coordinates exist in both cadastre and planning coordinate system were determined. By using, the coordinates of these seventeen points, the following transformation parameters were computed. Transformation equations are; Y^Aoa + A,,. Y+A12.X X=Ao,+A".X-A12.Y By using, transformation parameters in these equations, the coordinate of a point can be transformed into the another coordinate system. In ail these transformation process, Helmert's Similarity Transformation Method was used. The changes of city plan were studied too. For this purpose, an example of changing plan accepted in 1993 by Tokat municipality was selected and its original status was compared to its changed status. As a result, it was found out that the total cost/action coefficient were risen from 30 percent to about 45 percent As it is seen, this is a very bad thing for city plans homogenious. Therefore, the changing rules of city plans were explained according to planning rules. Finally, Tokat Main Triangulation was studied. Firstly, each triangulation was adjusted in its own inside then together. In figure 2, Tokat Main Triangulation Network was given. Figure 2 : Tokat Main Triangulation Network XI When Tokat Main Triangulation Network was adjusded, it was seen that there were no outliers until 1983 In 1983, a new planning work was done. And some sides that were calculated in old triangulation were directly measured by electro-optic device. When these measurements were compared, a scale difference was determined. An example of these measurements were given in figure 3. -:;SLp.k^.3:._::i I'lfe*.: elektrB^optI^üzünLuköLçü ve hesabi: Avj-ioo, £.İolî- :,U-Mr Oüsfıy Açı I. Omum II. Durum I !? II.100- (I Ml). AZ I '..', AZ i ± '!, <\z - z ILL 1İ..J/ <$fj>. tj6.a:.û:bii. ' '''ILL J72. M 'İTA: i....-.h 3]LJlA21 "t jbjJrıüS? 3A':Şy32/> : i hi JS 'j, UiO r "» 3o Eğik uzunluk d in mm * 'IfVS. i 38 -V6 ?.?.o/ \3M i 33.7. 1 23? ? ZU l!l^..İli. «-er 1 u» k e^-^v r-ürlt'. 5K, 7.9 S Î.9S <.. 2'/,!. (/. "?!? 0ı r:u ve 111 ".ı\r;ı yapam /, - / ) /..-' \) /&^J)- K0NTI101. HOİTH.. Mnr.ıB^Ö7THRr;NOnCI Figure 3 : Comparision of the distance value calculated in 1963 and the distance value directly measured in 1983 By using these new distance measurements, the triangulation was coordinated again. Hence, a new planning coordinate system was set up in Tokat and the cadastre and the planning coordinate system's homogenious was broken in Tokat. In 1986, in the another planning work, the coordinate system that was set up in 1963 was used in order to set up new necessary points. In 1989, in the another planning work, the coordinate system that was set up in 1983 was used again in order to set up new necassary points. XII Hence, we can say, the problems related to Tokat Main Triangulation Network started in 1983. In 1986 and in 1989, the problem became more and more complex due to carelessness and it has waited a solution since 1983. As a result, in order to solve problems related to cadastre and planning works in Tokat, The National Coordinate System should be taken as a base coordinate system and all plannig works that will be done in future should be done in this coordinate system. But, firstly the points of this coordinate system must be multiplied in a homogen work.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Jeodezi ve Fotogrametri; Kadastro; Tokat; Zoning plans; Geodesy and Photogrammetry; Cadaster; Zoning plans